2001
DOI: 10.1177/146900470100500303
|View full text |Cite
|
Sign up to set email alerts
|

Staff Knowledge about Symptoms of Mental Health Problems in People with Learning Disabilities

Abstract: The present study examined the knowledge of 116 health and social care staff working in learning disability services about the symptoms of mental health problems in this client group, using the Mini PAS-ADD as a comparator. Seventy-one percent of participants currently supported a client with mental health problems and learning disabilities; however, only 47 percent had received any training in this area. The health staff scored significantly higher than the residential and day care staff in relation to knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…As such, it accurately reflected current training resources and practices and could be readily adopted by services. As in previous research (Mester 1999; Quigley et al. 2001) the study found evidence to suggest that training was associated with increased knowledge of psychopathology.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As such, it accurately reflected current training resources and practices and could be readily adopted by services. As in previous research (Mester 1999; Quigley et al. 2001) the study found evidence to suggest that training was associated with increased knowledge of psychopathology.…”
Section: Discussionsupporting
confidence: 79%
“…Measuring knowledge of psychopathology more directly by using the Mini PAS‐ADD (Prosser et al. 1997) as a comparator, Quigley et al. (2001) conducted a postal survey of 116 health and social care staff working in intellectual disability services.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that the percentage of frontline staff trained to recognize mental illness among those with an intellectual disability is low. In a study of 116 health and social care staff, only 47% of those supporting a client with a mental health problem and an intellectual disability had received any specialist mental health training (Quigley, Murray, Mckenzie, & Gordon, 2001). Similar findings were reported by Bates, Priest, and Gibbs (2004) who suggested that care staff had received little or no training, and few had access to screening or assessment tools.…”
Section: Introductionmentioning
confidence: 99%
“…Staff knowledge in this area has been widely studied (e.g. Bates et al, 2004;Costello, 2005;Mohr et al, 2002;Quigley et al, 2001), with most studies identifying inadequate knowledge and limited relevant training, despite the introduction of national vocational qualifications in the UK (such as the Learning Disability Awards Framework (LDAF), 2009 and the Learning Disability Qualification (LDQ), 2010). It is worth noting that LDQ and LDAF have ceased to exist as of 2011 and have been replaced by the Common Induction Standards.…”
Section: Staff Training and Knowledgementioning
confidence: 99%